(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
Gestational surrogacy involves numerous legal issues that vary significantly across different jurisdictions. The complexity of these legal issues arises from the involvement of multiple parties (the intended parents, the surrogate mother, the child, and the clinics that offer reproductive services). The main bioethical and legal issues associated with gestational surrogacy, its relationship with human rights standards, credible legal solutions will be analyzed in the present paper.